Pengaruh Ukuran Kinerja Keuangan Tradisional dan Value Based Management terhadap Market Value Added pada Perusahaan Badan Usaha Milik Negara di Bursa Efek Indonesia - Andini Vatiady; Fajar Gustiawaty Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study examines the impact of traditional financial performance measures and Value-Based Management on Market Value Added (MVA) in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique employed was purposive sampling, resulting in the selection of 19 companies based on predetermined criteria. Secondary data was obtained from the Indonesia Stock Exchange website, and panel data regression analysis was used for data analysis. The results indicate that ROA and EVA positively and significantly influence MVA. In contrast, ROE, DPS, EBITDA, and CFROI do not significantly affect MVA. Notably, EPS demonstrates a negative impact on MVA, suggesting that higher earnings per share may not correlate with increased market value.